Reward sensitivity following boredom and cognitive effort: A high-powered neurophysiological investigation. (4th February 2019) - Milyavskaya, Marina; Inzlicht, Michael; Johnson, Travis; Larson, Michael J.
Abstract: What do people feel like doing after they have exerted cognitive effort or are bored? Here, we empirically test whether people are drawn to rewards (at the neural level) following cognitive effort and boredom. This elucidates the experiences and consequences of engaging in cognitive effort, and compares it to the consequences of experiencing boredom, an affective state with predicted similar motivational consequences. Event-related potentials were recorded after participants (N = 243) were randomized into one of three conditions – boredom (passively observing strings of numbers), cognitive effort (adding 3 to each digit of a four-digit number), or control. In the subsequent task, we focused on the feedback negativity (FN) to assess the brain's immediate response to the presence or absence of reward. Phenomenologically, participants in the boredom condition reported more fatigue than those in the cognitive effort condition, despite reporting exerting less effort. Results suggest participants in the boredom condition exhibited larger FN amplitude than participants in the control condition, while the cognitive effort condition was neither different from boredom nor control. The neural and methodological implications for ego depletion research, including issues of replicability, are discussed. Highlights: A boredom induction led to more subjective fatigue than a cognitive effort condition. Reward sensitivity larger following boredom condition than control condition. Reward sensitivity following cognitive effort did not differ from boredom nor control. No relation between self-report fatigue and reward sensitivity.